Label-free molecular imaging and discrimination of stem cells by Raman micro-spectroscopy - Ghita, Adrian (2014)
This thesis is focused on the development of Raman micro-spectroscopy for label free imaging and discrimination of stem cells. The thesis is divided into six chapters. Chapter 1 gives an overview of the existing techniques used for molecular analysis of cells, with emphasis on methods that allow non-invasive label-free imaging. A literature review of the main relevant applications of Raman micro-spectroscopy for imaging cells was also included. Chapter 2 discusses the basic theoretical principles of Raman scattering and design of Raman micro-spectrometers. The practical aspects related to the design of an optimised Raman micro-spectrometer are presented in Chapter 3 along with experimental characterisation of its performance. The chapter concludes with examples of Raman spectral maps of endothelial cells. Chapter 4 and Chapter 5 present experimental results obtained by Raman micro-spectroscopy for molecular analysis of live neural and mesenchymal stem cells. In these investigations Raman spectroscopy was used to identify, image and quantify spectral markers for label-free discrimination between glial cells and their neural progeny. The potential of Raman micro-spectroscopy to measure timecourse molecular changes of individual bone nodules was demonstrated in Chapter 5. Future work and final conclusion are discussed in Chapter six of this thesis.